2012
DOI: 10.3928/01477447-20120822-25
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Lower-extremity Long-bone Fractures in Active, Nonambulatory, Wheelchair-bound Patients

Abstract: A retrospective review of surgically treated lower-extremity long-bone fractures in wheelchair-bound patients was conducted. Between October 2000 and July 2009, eleven lower-extremity fractures in 9 wheelchair-bound patients underwent surgical fixation. The Short Musculoskeletal Function Assessment, Short Form, and Spinal Cord Injury Quality of Life questionnaires were used to assess functional outcome. Mechanism of injury for all patients was a low-energy fall that occurred while transferring. Four patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…The rationale for the operative management of long bones in paralysed limbs is based on the early return to previous activities and high patient satisfaction. 2,13 However, strong recommendations concerning operative or conservative treatment of long-bone fractures in SCI individuals cannot be drawn from our data, due to the retrospective study design. For this purpose, prospective controlled interventional studies would be required.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The rationale for the operative management of long bones in paralysed limbs is based on the early return to previous activities and high patient satisfaction. 2,13 However, strong recommendations concerning operative or conservative treatment of long-bone fractures in SCI individuals cannot be drawn from our data, due to the retrospective study design. For this purpose, prospective controlled interventional studies would be required.…”
Section: Discussionmentioning
confidence: 82%
“…12 However more recently, operative fracture management has been advocated. 2,13 Generally, the goal of fracture management is the restoration of the level of prefracture activity and functioning of the patient. 2,4 As a consequence, an individual approach to fracture treatment has been recommended.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, others have reported that nonsurgical treatment of fractures may be associated with complications 7,[27][28][29] and have observed good outcomes with primary surgical treatments. 32 In addition, several studies have suggested that surgical treatment of fractures in SCI patients may expedite post-fracture mobilization. 26,32 Conversely, other reports 9,28,33,34 have found nonsurgical treatments to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…32 In addition, several studies have suggested that surgical treatment of fractures in SCI patients may expedite post-fracture mobilization. 26,32 Conversely, other reports 9,28,33,34 have found nonsurgical treatments to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, Sugi et al 19 successfully treated 11 cases either by ORIF or by intramedullary nailing. The interesting fact of that study is that patients reached the initial life quality measured by the performed questionnaires.…”
Section: Discussionmentioning
confidence: 99%